The limit of discounted utilitarianism - Adam Jonsson; Mark Voorneveld (Stockholm School of Economics, The Economic Research Institute (EFI), 2014)
This paper presents an infinite-horizon version of intergenerational utilitarianism that is both satisfactorily complete and consistent. By studying discounted utilitarianism as the discount factor tends to one, we obtain a welfare criterion - limit-discounted utilitarianism - that combines efficiency and the equal treatment of generations with analytical tractability and a high degree of comparability. We show that limit-discounted utilitarianism satisfies a number of consistency properties; in particular, it provides (i) an intuitive link between preferences over infinite-horizon streams and large, but finite-horizon truncations, and (ii) a complete view of the consequences of delaying streams with well-defined finite averages. The latter is formulated through a principle of compensation. Through this compensation principle, limit-discounted utilitarianism gives a coherent view on the consequences of delaying welfare which is compatible with stationarity. Limit-discounted utilitarianism is characterized on a large domain of infinite-horizon utility streams.
Keywords: D63; D70; D90; 330; intergenerational equity; aggregating infinite utility streams; ethical social welfare relations